Clinical Approach to Flash Glucose Monitoring: An Expert Recommendation. (January 2020) - Chico, Ana; Aguilera, Eva; Ampudia-Blasco, Francisco Javier; Bellido, Virgina; Cardona-Hernández, Roque; Escalada, Francisco Javier; Fernández, Diego; Gómez-Peralta, Fernando; González Pérez de Villar, Noemí; Gorgojo, Juan José; Mezquita-Raya, Pedro; Morales, Cristóbal; et al.
The flash glucose monitoring (FGM) system FreeStyle Libre® is a device that measures interstitial glucose in a very simple way and indicates direction and speed of glucose change. This allows persons with diabetes to prevent hypoglycemic and hyperglycemic events. Scientific evidence indicates that the system can improve glycemic control and quality of life. To obtain the maximum benefit, it is necessary to properly handle glucose values and trends. Due to the generalization of the system use, the purpose of the document is to provide recommendations for the optimal use of the device, not only in the management of glucose values and trends but also in the prevention of hypoglycemia, actuation in exercise, special situations, and retrospective analysis of the glucose data, among others.